Changes in cardiovascular disease risk factors from age 9 to 19 and the influence of television viewing1. (26th March 2013) - Mitchell, Jonathan A.; Pate, Russell R.; Liese, Angela D.
Abstract: Objective: The purpose of this study was to determine if time spent watching television is associated with changes in cardiovascular disease (CVD) risk factors from age 9 to 19. Design and Methods: Participants were girls enrolled in the NHLBI Growth and Health Study ( n = 1, 702), and CVD risk factors were measured at ages 10, 12, 14, 16, and 19. Longitudinal quantile regression was used to determine if television viewing was associated with changes in CVD risk factors over time at the 10th, 25th, 50th, 75th, and 90th percentiles of the CVD risk factors. Results: In black girls, television viewing (h/wk) was positively associated with sum of skinfolds (mm) at the 75th (0.22, 99% CI, 0.06‐0.38) and 90th percentiles (0.21, 99% CI, 0.05‐0.36), but not at the 10th, 25th, or 50th percentiles. In white girls, television viewing (h/wk) was positively associated with sum of skinfolds (mm) with the strength of the associations progressively stronger toward the upper tail of the skinfold distribution, adjusting for physical activity and other covariates (10th percentile: 0.08, 99% CI, 0.03‐0.13; 90th percentile: 0.42, 99% CI, 0.24‐0.59). All associations were adjusted for physical activity, dietary factors, sleep, and maturation. No associations were observed between television viewing and changes in systolic blood pressure, triglycerides, or cholesterol levels in black or white girls. Conclusion: Girls who spent more time watching television had greater increases in sum of skinfolds from age 9 to 19, independent of physical activity levels and other covariates. The associations observed were stronger at the upper tail of the skinfold distribution.